ANALISIS PROFESIONALISME GURU PAI DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK PADA ERA KURIKULUM MERDEKA - Nur Hafiidah, Revalina; Miftakhul Fauzia; Shohibul hidayah; Munawir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students' religious character amidst current social changes and technological developments. This study was conducted to evaluate the effect of Islamic Religious Education (PAI) teacher professionalism on the development of students' religious character within the Kontur Merdeka (Freedom Contour) program. The research employed a qualitative method, primarily analyzing literature on this topic from several scientific journals. The findings indicate that Islamic Religious Education (PAI) teacher professionalism significantly influences religious character formation through role models, habit formation, and the implementation of innovative learning models. Furthermore, Kontur Merdeka creates opportunities for teachers to explore religion through novel approaches. However, several challenges, such as the influence of digital media, lack of environmental supervision, and limited skills, must be addressed in developing skills in the education sector. Therefore, Islamic Religious Education (PAI) teacher professionalism is a crucial element in the development of religious character.